PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR SEGITIGA DAN SEGIEMPAT MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF MAKE A MATCH - Suwarsi, Tri Unggul; Pujianto, Pujianto (Journal of Honai Math, 2018)
This classroom action research (CAR) aimed to: improve student’s activities and mathematics learning outcomes subject triangle and square for the student at class VII B of SMP Negeri 5 Surakarta through the implementation of the Make a Match cooperative learning model. This study used the method of CAR which was carried out during March until July 2018, and it was in the 2017/2018 academic year. The receptive subject of the study was the 29 students of VII B while the agent subject was the mathematics teacher. The data were collected by observation, test, and documentation. The data were then analyzed using the technique of comparative descriptive statistic and critical analysis. The result of CAR shows that the implementation of cooperative learning model type make a match can improve the student’s activities and student’s mathematics learning outcome. DOI: https://doi.org/10.30862/jhm.v1i2.1047